PENGARUH PEMBERIAN PAKAN KEONG MAS TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP KEPITING BAKAU SISTEM SINGLE ROOM - Muhammad Agus; HADI Pranggono; Harun Murtadlo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
AbstractThe  Maintenance  of mangrove crabs single  room system requires the  provision  of food  in quantity and good quality, cheap, on time and deliver high production value. One of the available food for  the  growth  of mangrove crabs in Central  Java is  the golden  apple  snail (Pomacea canaliculata), which has a protein content reached 51%. This study aims to determine the effect of feeding fresh golden apple snail with different doses on the growth and survival of mangrove crabs in  a single  room in  the pond system. The  study  consisted of five treatments fresh  golden apple  snail fresh feed at  a  dose  of 5.7,  9,  11 and  13%  / BW/day)  with  5 replications.  The experiment conducted at the beginning of mangrove crabs weigh between 80-100 g. Parameters measured include weight  gain during maintenance,  feed  efisiansi, survival and quality  of  the waters. The results showed, the highest weight gain observed in the treatment of 9% amounting to 92.2 g, while the lowest weight gain observed in the treatment of 5% amounting to 56.6 g. There was no difference in survival in each treatment feed, with the highest survival rate of 100%. The lowest feed  efficiency is  toun  the  treatment of  feed contained 13% of 41.61%.  During  the research, the parameters of qualities water in all treatments was within the range for the growth of mangrove crabs. Keywords: Scylla serrata, golden apple snail, growth, survival, feed efficiency